Oxidative dehydrogenation of C–C and C–N bonds: A convenient approach to access diverse (dihydro)heteroaromatic compounds - Hati, Santanu; Holzgrabe, Ulrike; Sen, Subhabrata (Beilstein Journal of Organic Chemistry, 2017)
Nitrogen heteroarenes form an important class of compounds which can be found in natural products, synthetic drugs, building blocks etc. Among the diverse strategies that were developed for the synthesis of nitrogen heterocycles, oxidative dehydrogenation is extremely effective. This review discusses various oxidative dehydrogenation strategies of C–C and C–N bonds to generate nitrogen heteroarenes from their corresponding heterocyclic substrates. The strategies are categorized under stoichiometric and catalytic usage of reagents that facilitate such transformations. The application of these strategies in the synthesis of nitrogen heteroarene natural products and synthetic drug intermediates are also discussed. We hope this review will arouse sufficient interest among the scientific community to further advance the application of oxidative dehydrogenation in the synthesis of nitrogen heteroarenes.
Keywords: aerobic oxidation; bioinspired Flavin mimics; nitrogen heteroarenes; organo catalytic; oxidative dehydrogenation